1997
DOI: 10.1007/bf02070713
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of occult tumor cells in lymph nodes of colorectal carcinomas

Abstract: The results show that occult tumor cells might increase the risk for development of a local tumor relapse and/or distant metastases but do not influence patients' prognoses at all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
3
12

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 16 publications
2
78
3
12
Order By: Relevance
“…O reestadiamento a partir da detecção do envolvimento micrometastático pode não ter implicações clíni-cas objetivas, uma vez que os resultados deste estudo, a exemplo dos de outros autores 1,5,13,[18][19][20] , revelaram ausên-cia de impacto negativo da presença de micrometástases na sobrevivência dos doentes submetidos à extirpação curativa do carcinoma colorretal. Por outro lado, outros investigadores sustentaram que a identificação de micrometástases linfonodais teria influência negativa na sobrevivência dos seus portadores 3,17,21 .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…O reestadiamento a partir da detecção do envolvimento micrometastático pode não ter implicações clíni-cas objetivas, uma vez que os resultados deste estudo, a exemplo dos de outros autores 1,5,13,[18][19][20] , revelaram ausên-cia de impacto negativo da presença de micrometástases na sobrevivência dos doentes submetidos à extirpação curativa do carcinoma colorretal. Por outro lado, outros investigadores sustentaram que a identificação de micrometástases linfonodais teria influência negativa na sobrevivência dos seus portadores 3,17,21 .…”
Section: Resultsunclassified
“…O carcinoma colorretal é uma das doenças malignas mais freqüentes no mundo ocidental e sua incidência está em elevação 1 . Apesar do uso de diferentes procedimentos diagnósti-cos, no momento da cirurgia muitos doentes apresentam o tumor em estádio avançado e nos enfermos com lesões extirpá-veis a sobrevivência de cinco anos atinge somente cerca de 50% 2,3 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Conversely, Liefers et al reported that presence of MM in SLN has a significant impact on overall survival in colorectal patients. For patients having no metastases detected 5 years survival rates were 91% while for those found positive for MM 5 years survival rates were merely 50% (p=0.02) (36). In 2002 Rosenberg confirmed that presence of MM is a statistically significant factor influencing long-time survival rates [38].…”
Section: Legend: Ptnm -Pathological Classification Of Malignant Tumoumentioning
confidence: 97%
“…In the recent years several reports were published on the role of MM and/or ITC in CRC in relation to risk of local recurrence, the risk of distant metastases and the impact on patient's prognosis. Broll et al suppose that the presence of MM in SLN detected by IHC might result in higher rates of local recurrences and distal metastases, however there is no effect on overall survival of the patients [36]. Conversely, Liefers et al reported that presence of MM in SLN has a significant impact on overall survival in colorectal patients.…”
Section: Legend: Ptnm -Pathological Classification Of Malignant Tumoumentioning
confidence: 99%